High Stakes : Big Time Sports and Downtown Development - Curry, Timothy J. (Timothy Jon), 1943-; Woldoff, Rachael; Schwirian, Kent P.; Project Muse. (Columbus : Ohio State University Press, 2004)
Unlike so many other cities around the country, Columbus citizens gave a firm "no" to the proposal that public money be used to build an arena to attract an expansion professional hockey team and a soccer stadium to keep a professional franchise. Yet, both structures are now a permanent part of Columbuss landscape. High Stakes is the inside story of how a coalition of the city's movers and shakers successfully did an end-run around the electorate to build these sports complexes. As it turned out, everybody appears to have won: taxpayers were relieved of any funding obligation, the coalition got the new facilities, and the new arena jumpstarted downtown redevelopment. Now, the Columbus case is being touted as the model of how to use professional sports to improve a city's downtown with minimal taxpayer expense. [Publisher web site]
Sports facilities, public funding, and community conflict -- The stadium game -- Sports and the urban redevelopment game -- Columbus: facts, image, games, and players -- Issue 1: To build an arena and a stadium -- From win-lose to win-win -- Beyond the arena district: downtown Columbus (with Benjamin Cornwell) -- Other cities, other games (with Benjamin Cornwell) -- Appendix: The Ecology of Games Social Action Model (with Benjamin Cornwell).
Description based on print version record.
Keywords: Urban renewal; Sports -- Social aspects; Sports -- Economic aspects; Professional sports -- Social aspects; Professional sports -- Economic aspects; Community development; Renovation urbaine -- Ohio -- Columbus; Developpement communautaire -- Ohio -- Columbus; Sports professionnels -- Aspect economique -- Ohio -- Columbus; Sports -- Aspect economique -- Ohio -- Columbus; Sports professionnels -- Aspect social -- Ohio -- Columbus; Sports -- Aspect social -- Ohio -- Columbus; Urban renewal -- Ohio -- Columbus; Community development -- Ohio -- Columbus; Professional sports -- Economic aspects -- Ohio -- Columbus; Sports -- Economic aspects -- Ohio -- Columbus; Professional sports -- Social aspects -- Ohio -- Columbus; Sports -- Social aspects -- Ohio -- Columbus; Ohio -- Columbus; Electronic books